Literature review for the topic of automation of scheduling classes and exams in higher education institutions - Wadhah M Al-Gabri (Advanced Engineering Research)
Introduction. Schedules of classes and exams are crucial components in the training process organization. Their quality directly affects the successful mastering of learning materials and ensures physical and psychological health of the educational process participants. The influence of educational systems features on the problem setting and solving methods under timetabling is considered. The emphasis is upon the timetabling problems in the higher education systems. Materials and Methods. The analytical study results of a number of the Russian and foreign sources on methods and algorithms of the classes and exams timetabling automation are described. These techniques and algorithms are compared from the standpoint of modern system-analysis methods. Schedule is considered as part of the educational process support system, and, in its turn, has features of the system combining such objects as students, teachers, disciplines, and classrooms. The application of the system analysis methods allows allocating essential features of the implemented systems of timetabling, classifying and evaluating them. Research Results. It is found that the tasking of classes scheduling and exams timetabling are practically equivalent and include the timetable quality criterion, soft and hard constraints. Russian sources contain detailed studies of various tasks of the classes timetabling. At the same time, no papers devoted to developing methods and algorithms for the examination schedules are found among these sources. However, foreign sources are largely devoted to the examination schedules. Graph theory methods, heuristic and hybrid optimization algorithms, linear integer programming techniques, system analysis methods, and other modern techniques of discrete mathematics are applied to solve the problems in hand. Discussion and conclusions. In general, in one and the same institution, the dimension, as well as the solution to the examination scheduling problem is less complicated than the classes scheduling. In connection with the expansion of the individualization of the learning process in the Russian educational system, the improvement of the research methods and algorithms relevance for constructing exams schedule is expected.